Analysis of consumer acceptability of green bean flour as a substitution for wheat flour in baked sponge cake - Wijaya, Selvyani; Rosanto, Stephanie; Christin, Lelly (Universitas Wiralodra, 2023)
Green Beans are one commodity the nuts spread in Indonesia can replace material food that can become Lots of food. Plus, peanuts green can make as flour, peanut green can give Lots of benefits. Using peanut green flour on manufactured cake dry also helps reduce high gluten content, which is Good for the body. Another benefit can support the diversification of products of enough food tall from the import process. With existing flour, peanut green can replace flour. Study This use study experiment uses a purposeful hedonic test to measure the level of liking and power by accepting the public with substitute flour wheat use flour peanut green to manufacture cake sponge roast. This research uses five samples of cake sponge roast with flour peanut green and one sample of cake sponge roast original as sample C has almost the same value comparison. Power tests accept consumers, carried out at SMK N 4 Jambi City with 100 Panelists who are students majoring in catering/patisserie. Analysis results show that the fifth sample owns relatively the same color. However, in the hedonic test, sample A gets a treatment of 3.02 %. Sample C has the best aroma compared to sample other with test results of 3.25%, for aspect texture obtained by sample B with a value of 3.12%, and for taste obtained by sample D with a value of 3.46 %. The fifth average result sample has almost the same value, ± 3.00%. Which is where all samples can be accepted and liked by society.